Tindak Tutur Ekspresif dalam Film Milly dan Mamet Sutradara Ernest Prakasa - Indah Marfaelas; Ermawati Arief (Universitas Negeri Padang, 2023)
ABSTRACTThe purpose of this study was to describe the forms of expressive acts in the film Milly and Mamet directed by Ernest Prakasa, to describe the speech strategies in the film Milly and Mamet directed by Ernest Prakasa, and their implications for learning Indonesian. This type of research is a qualitative research with descriptive method. The research became a research instrument in this research. The data of this research are all expressive speech acts of speakers and partners in the film Milly dan Mamet directed by Ernest Prakasa from beginning to the end. The data collection technique is the note-taking technique in this research is a detailed desriptive technique. Data analysis techniques consist of four steps, a) data identification, b) data classification, c) data interpretation, and d) making conclusions. Based ond the results of this research, the most dominant expressive speech act used in Ernest Prakasa film Milly and Mamet is the expressive speech act to blaming while the least used expressive speech act is the expressive speech act to expressing condolences. In the Ernest Prakasa directed film Milly and Mamet, the most dominant speech strategy used was speaking frankly without preamble, while the least used speech strategy was vague. This research has implications for learning Indonesian in the response text of class IX students in odd semesters. Keywords: Expressive speech acts; speaking strategy; film Milly and Mamet.